Light-induced relief gratings and a mechanism of metastable light-induced expansion in chalcogenide glasses - Messaddeq, S. H.; Tikhomirov, V. K.; Messaddeq, Younes [UNESP]; Lezal, D.; Li, M. S. (American Physical Soc, 2001)
We report on a metastable light-induced volume expansion in Ge25+xGa10-xS65 glasses under irradiation with band gap (UV) light, which can result in recording of relief gratings on their surface in the case of irradiation with two interfering beams. We propose a mechanism for the expansion, which is based on the light-induced change in the polarizability of secondary (van der Waals type) bonds and the effect of this change on primary (covalent type) bonds of the glass. The effect is suggested to be due to an interference of electrons, which belong to a chalcogen atom and participate in the formation of secondary and primary bonds, respectively. We suggest that a minimum point of the Lennard-Jones potential, which corresponds to the equilibrium position of a chalcogen atom is shifted in the course of irradiation to a larger interatomic distance. This shift causes a volume expansion and allows a diffusion of chalcogen atoms into the irradiated area. We show that light-induced polymerization of the glass network is an important attribute of the light-induced volume expansion.